1996
DOI: 10.1159/000106599
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Effect of <i>Ginkgo biloba</i> Extract (EGb 761) on the Activity of Presynaptic Cholinergic Nerve Terminals in Rat Hippocampus

Abstract: The effects of Ginkgo biloba extract (EGb) applied in vitro to hippocampal synaptosomes from young Wistar rats on the specific binding of [3H]hemicholinium-3 ([3H]HCh-3), high-affinity choline uptake (HACU) and activity of Na+,K+-ATPase were examined. EGb at a concentration of 100 µg/ml markedly elevated the specific binding of [3H]HCh-3 (to 306%) and moderately elevated HACU values (to 115%). Scatchard analysis revealed an increase in the Bmax Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The exact mechanism through which GKB modulates β-amyloid-suppressed ACh remains unknown. However, it is of interest to note that β-amyloid peptides have been shown to reduce high affinity choline uptake (Kristofikova et al, 2001), whereas ginkgo extract (EGb 761) has been reported to increase choline uptake in the hippocampal synaptosomes (Kristofikova and Klaschka, 1997). Therefore, GKB could have a direct effect in reversing the inhibitory effect of β-amyloid peptides by altering central cholinergic activities.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism through which GKB modulates β-amyloid-suppressed ACh remains unknown. However, it is of interest to note that β-amyloid peptides have been shown to reduce high affinity choline uptake (Kristofikova et al, 2001), whereas ginkgo extract (EGb 761) has been reported to increase choline uptake in the hippocampal synaptosomes (Kristofikova and Klaschka, 1997). Therefore, GKB could have a direct effect in reversing the inhibitory effect of β-amyloid peptides by altering central cholinergic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Droy-Lefaix 1997; Hibatallah et al, 1999;Siddique et al, 2000), modulation of a number of neurotransmitter systems (e.g. Taylor, 1986;Ramassamy et al, 1992;Huguet et al, 1994;Kristoikova and Klaschka, 1997), beneficial effects on blood circulation (e.g. Jung et al, 1990;Koltringer et al, 1993;Krieglstein et al, 1986;Chung et al, 1999;Topp et al, 2001), both in vitro and in vivo protection against hypoxic challenges (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…More recent evidence has shown that Ginkgo biloba also acts as an inhibitor of the monoamine metabolizing enzymes, monoamine oxidase A and B, which may also contribute to its free-radical scavenging and neuroprotective effects (White et al, 1996). In addition, evidence suggests that both acute and chronic doses of Ginkgo biloba may modulate the cholinergic system (Nathan, 2000), with direct effects on choline uptake and acetylcholine release (Kristofikova and Klaschka, 1997) and increases in cholinergic muscarinic receptors (Taylor, 1986).…”
Section: Introductionmentioning
confidence: 99%